Reconstructing the Principle of Legal Certainty as an Object of the Honorary Board of Election Organizers - Noval Katili; Erman I. Rahim; Zamroni Abdussamad (International Journal of Sociology and Law, 2025)
This article aims to know and analyze efforts to reconstruct the principle of legal certainty which is the object of the case in the Ethics Court of the Ethics Council of the Election Organizer in Indonesia. This research uses normative legal research methods or doctrinal legal research. This article shows that there is legal uncertainty in the regulation of the Ethics Council of Election Organizers. Therefore, this article provides recommendations for specific arrangements regarding legal certainty that become material elements of the case that can be submitted to the Honorary Council of Election Organizers.